2020
DOI: 10.1038/s41388-020-01389-7
|View full text |Cite
|
Sign up to set email alerts
|

MEIS1 down-regulation by MYC mediates prostate cancer development through elevated HOXB13 expression and AR activity

Abstract: Localized prostate cancer develops very slowly in most men, with the androgen receptor (AR) and MYC transcription factors amongst the most well-characterized drivers of prostate tumorigenesis. Canonically, MYC up-regulation in luminal prostate cancer cells functions to oppose the terminally differentiating effects of AR. However, the effects of MYC up-regulation are pleiotropic and inconsistent with a poorly proliferative phenotype. Here we show that increased MYC expression and activity are associated with th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 43 publications
(58 reference statements)
0
20
0
Order By: Relevance
“… 6 , 7 , 29 However, there is debate when it comes to the role of MEIS1 in solid tumors. The controversy is reflected in the potential tumor-suppress role of MEIS1 in prostate cancer 30 and clear cell renal cell carcinoma 31 and that depletion of MEIS1 as well as MEIS2 enhanced tumor growth by upregulating c-MYC and CD142, 7 but the oncogenic role of MEIS1 in glioma. 32 , 33 Therefore, the functions of MEIS1 in different solid tumors need to be further elaborated.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 , 29 However, there is debate when it comes to the role of MEIS1 in solid tumors. The controversy is reflected in the potential tumor-suppress role of MEIS1 in prostate cancer 30 and clear cell renal cell carcinoma 31 and that depletion of MEIS1 as well as MEIS2 enhanced tumor growth by upregulating c-MYC and CD142, 7 but the oncogenic role of MEIS1 in glioma. 32 , 33 Therefore, the functions of MEIS1 in different solid tumors need to be further elaborated.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of MYC decreases MYC occupancy at the MEIS1 locus and leads to downregulation of MEIS1. On the other hand, knockdown of MYC activity leads to increased expression of MEIS1, following an increased occupancy of MYC at the MEIS1 locus [115]. In addition, in prostatic cancer tissues, statistically significant positive correlations between MYC and HOXB13 mRNA levels was observed [115], while an independent group confirmed that the tumor-suppressive activity of MEIS1 was dependent on HOXB13 [116].…”
Section: The Role Of Meis1 In Solid Cancersmentioning
confidence: 93%
“…MEIS1 has been associated with a variety of solid cancers, including prostate, non-small cell lung and gastric cancer, as well as clear cell renal cell carcinoma, esophageal squamous cell carcinoma, malignant peripheral nerve sheath tumors and Ewing sarcoma. The MYC-mediated downregulation of MEIS1 upregulates the androgen receptor (AR) to promote prostate cancer cell proliferation ( 64 ). AR transcription is inhibited by the overexpression of MEIS1 and is promoted by MEIS1 knockdown with small interfering RNA ( 49 ).…”
Section: Role Of Meis1 In the Proliferation Of Cancer Cellsmentioning
confidence: 99%